MHY2233 Attenuates Replicative Cellular Senescence in Human Endothelial Progenitor Cells via SIRT1 Signaling. (22nd May 2019) - Lamichane, Shreekrishna; Baek, Sang Hong; Kim, Yeon-Ju; Park, Ji Hye; Dahal Lamichane, Babita; Jang, Woong Bi; Ji, SeungTaek; Lee, Na Kyung; Dehua, Li; Kim, Da Yeon; Kang, Songhwa; Seong, Ha Jong; et al.
Abstract : Cardiovascular diseases (CVDs) are a major cause of death worldwide. Due to the prevalence of many side effects and incomplete recovery from pharmacotherapies, stem cell therapy is being targeted for the treatment of CVDs. Among the different types of stem cells, endothelial progenitor cells (EPCs) have great potential. However, cellular replicative senescence decreases the proliferation, migration, and overall function of EPCs. Sirtuin 1 (SIRT1) has been mainly studied in the mammalian aging process. MHY2233 is a potent synthetic SIRT1 activator and a novel antiaging compound. We found that MHY2233 increased the expression of SIRT1, and its deacetylase activity thereby decreased expression of the cellular senescence biomarkers, p53, p16, and p21. In addition, MHY2233 decreased senescence-associated beta-galactosidase- (SA- β -gal-) positive cells and senescence-associated secretory phenotypes (SASPs), such as the secretion of interleukin- (IL-) 6, IL-8, IL-1 α, and IL-1 β . MHY2233 treatment protected senescent EPCs from oxidative stress by decreasing cellular reactive oxygen species (ROS) levels, thus enhancing cell survival and function. The angiogenesis, proliferation, and migration of senescent EPCs were enhanced by MHY2233 treatment. Thus, MHY2233 reduces replicative and oxidative stress-induced senescence in EPCs. Therefore, this novel antiaging compound MHY2233 might be considered a potent therapeutic agent for the treatment of age-associated CVDs.